Hormonal and Temperature Manipulation to Produce Male Homogametic (XX) in Developing Female Monosex Culture of Thai Catfish Pangasionodon hypopthalmus - H. Arfah; O. Carman (Jurnal Akuakultur Indonesia)
The female of Thai catfish Pangasionodon hypopthalmus had higher growth rate, about 25-30% than male fish, especially on growth phase-2 when the fish get sexually mature. Monosex female fish culture system can increase production efficiency in term of time and cost.  Experiment was performed to get male homogametic (XX) that will be used as functional male to produce female monosex (XX) population Result of hormonal and temperature manipulation on larvae shown that the highest percentage of male (67.7%) was obtained by 5 mg/liter 17-α-metiltestosteron treatment with temperature 33oC. Good temperature for larva rearing was 30oC. The result of fertility test on male fish was fertile, but progeny test was not performed homogametic (XX) character yet.